Community Participation and Water Payment Compliance: A Case Study of Kitgum Town - Uganda - Nakaggwa, Rosemary; Obanda, Peter W.; Pule, Samuel (International Journal of Social Science and Humanities Research, 2016)
In this article, we examined the influence of community participation in planning, pricing and monitoring of water services on compliance to payment for water services taking Kit gum Town as a case study area. Using interviews and focus group discussions, we assessed 54 members of the Business Community Association and other political representatives in Kit gum on their level of participation in water service provision and compliance to payment for water. Frequency analyses were used to explore the extent of community participates in planning, pricing and monitoring of water services in Kit gum. Linear regression on the hand, were used to establish the influence of community participation in planning, pricing and monitoring of water services on compliance to payment for these services. Findings in the multiple regression summary revealed a positive relationship with the overall correlation (linear relationship) between compliance to payment (dependent variable) and community participation being r=0.56, which is consistent with recent research on community participation in water services, such as Magma (2013). The researchers therefore recommended that community participation should be expanded to include most of the sections of the community with programs to empower the community on effective participation and engagement techniques, and written effective distributed guidelines. Secondly, the need for regular community meetings on the water services and use of a far-reaching forum to communicate on meter prices, changes in water tariffs, and monitoring tools is paramount.
Keywords: Community Participation; Water Services Planning; Pricing for Water Services; Water Services Monitoring and Water Payment Compliance